Proceedings of the 12th International Conference on Natural Language Generation 2019
DOI: 10.18653/v1/w19-8606
|View full text |Cite
|
Sign up to set email alerts
|

Diamonds in the Rough: Generating Fluent Sentences from Early-Stage Drafts for Academic Writing Assistance

Abstract: The writing process consists of several stages such as drafting, revising, editing, and proofreading. Studies on writing assistance, such as grammatical error correction (GEC), have mainly focused on sentence editing and proofreading, where surface-level issues such as typographical, spelling, or grammatical errors should be corrected. We broaden this focus to include the earlier revising stage, where sentences require adjustment to the information included or major rewriting and propose Sentence-level Revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Similar to this is Grammatical Error Correction which seeks to correct errors such as grammar and punctuation (Ng et al, 2014;. Sentence revision (Ito et al, 2019) extends this to cases for which major rewriting may be needed. Sentence simplification (Nisioi et al, 2017) aims at using techniques such as shortening the sentences to make a text more readable.…”
Section: Sentence Editing and Simplificationmentioning
confidence: 99%
“…Similar to this is Grammatical Error Correction which seeks to correct errors such as grammar and punctuation (Ng et al, 2014;. Sentence revision (Ito et al, 2019) extends this to cases for which major rewriting may be needed. Sentence simplification (Nisioi et al, 2017) aims at using techniques such as shortening the sentences to make a text more readable.…”
Section: Sentence Editing and Simplificationmentioning
confidence: 99%
“…Previous works on iterative text revision have three major limitations: (1) simplifying the task to an noniterative "original-to-final" text paraphras-ing; (2) focusing largely on sentence-level editing Botha et al, 2018;Ito et al, 2019;Faltings et al, 2021); (3) developing editing taxonomies within individual domains (e.g. Wikipedia articles, academic writings) (Yang et al, 2017;Zhang et al, 2017;Anthonio et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2 Related Work and how effective their actions are (Yang et al, 2017;Zhang et al, 2017;Ito et al, 2019). However, these works do not further explore how to leverage edit intentions to generate better-revised documents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational modeling of the iterative text revision process is essential for building intelligent and interactive writing assistants. Most prior works on the development of neural text revision systems Botha et al, 2018;Ito et al, 2019;Faltings et al, 2021) do not take the iterative nature of text revision and human feedback on suggested revisions into consideration. The direct application of such revision systems in an iterative way, however, could generate some "noisy" edits and require much burden on human writers to fix the noise.…”
Section: Introductionmentioning
confidence: 99%